The Correlation Between Nutritional Status, Age, and Gender on the Incidence of Soil-Transmitted Helminth Infections - Nikmatullah, Nurul Azmah; Masyhuda, Irmawati; Permanasari, Etin Diah; Rahmadilla, Chintya (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
Soil-transmitted helminth (STH) infections most commonly infect preschool and school-age children. The prevalence of STH infection remains high, i.e., 73 million children are infected in Indonesia. The most commonly infecting worms are roundworms (Ascaris lumbricoides), whipworms (Trichuris trichiura), and hookworms (Ancylostoma duodenale and Necator americanus). STH infection is transmitted through soil contaminated by STH eggs or larvae. Personal hygiene, availability of clean water, and defecation behavior are factors in the development of STH infection. Prolonged infection can cause malnutrition, anemia, and slow growth. This study aims to examine the association between nutritional status, age, and gender on the incidence of STH infection. This research is a descriptive-analytical study with a cross-sectional approach. Fifteen (42.86%) of 35 preschool and school-age children's stool samples were positive for Ascaris lumbricoides eggs. The nutritional status of the children was grouped into underweight, normal, and overweight. The body mass index (BMI) calculation resulted in 65.71% (23/35) underweight, 31.43% (11/35) normal, and 2.86% (1/35) overweight children. The Spearmen test shows that there is no significant correlation between nutritional status (p=0.517), age (p=0.614), and gender (p=0.637) on STH infection.